Toward a comprehensive analysis of pesticide use in Cambodian rice farming and identification of levers for its reduction - Ngang Linna; Bureau-Point Eve; Or Phirum; Garnier Suzon; Hou Sorith; Heuclin Benjamin; Letourmy Philippe; Nguon Samnang; Sester Mathilde (Cahiers Agricultures)
This article reports on pesticide use in rice production by 210 farmers across seven provinces in Cambodia along a gradient of intensification defined by the number of rice crops per year. Using descriptive statistics and thematic analysis of both qualitative and quantitative data, we compare rice production systems with one, two, or three crops per year. The level of pesticide use was assessed through spraying frequency and the type of pesticide used, the pests targeted by farmers, and their active ingredients. The results indicate varying intensities of pesticide use, with the highest application rates per cycle, particularly of insecticides, in the three-crop rice system. Farmers primarily rely on advice from local pesticide sellers for their choice of product and application rate and often mix different pesticides to enhance efficacy. Through on-site visits, 68 different active ingredients were identifiedd on the labels of pesticide packages stored on farms. Farmers expressed concern about the health and environmental risks associated with pesticide use. Our study highlights the complex relationships between agricultural intensification and pesticide use, as well as the importance of tailored extension services that offer information, education, and training to help farmers mitigate the risks of intensive pesticide use. It also underscores the need for ongoing surveys to document agricultural practices in evolving systems.